108 Comparing autoimmune encephalitis variants in a pediatric cohort from Hamilton, Ontario. (29th October 2021) - Grinberg, Mark; Schneeweiss, Michelle; Povolo, Christopher; Inkaran, Jeyanth; Jones, Kevin
Abstract: Primary Subject area: Neurology Background: Autoimmune Encephalitis (AE) is an emerging cause of epilepsy with numerous variants, including anti NMDA-receptor encephalitis, for which there is a detectable antibody. However, it is believed that there are many variants of AE for which an antibody has not yet been discovered. Objectives: This study aimed to determine the differences in disease course of AE patients with and without detectable anti-NMDA receptor antibody. Design/Methods: This retrospective analysis is part of a Canada-wide project aimed at evaluating the epidemiology and characteristics of AE. Cases with suspected AE were retrieved and screened by two independent reviewers against AE criteria. Those that met criteria were analyzed for trends and stratified into NMDA receptor antibody positive (NMDAr) and negative categories for inter-group analysis. Of 23 cases reviewed, 11 met criteria (aged 1-17 years, 27% males), of which 7 were NMDAr positive. Results: The NMDAr subgroup was characterized by behavioural changes, focal seizures, and prodromal fever on presentation, whereas the receptor negative subset had a much higher variability of symptoms, without any distinctive patterns. On average, the NMDAr positive group showed an increase in white blood cell count on CSF analysis, and a slight increase in the proportion of patients presenting with supratentorial lesions on MRI. Both groups had abnormal findings on EEG. However, despite the lack of gross differences in findings, all of the NMDAr positive cases received IVIG (most with corticosteroids as well) while only 2 NMDAr negative patients received immunomodulatory therapy. At discharge 6/7 of the NMDAr patients had some form of residual movement disorder while the NMDAr negative group had more variable residual symptoms at discharge. Conclusion: Our findings show that a high index of suspicion in the diagnosis of AE is required due to the indistinct distribution and variety in its presentation. Negative antibody findings should not rule out AE due to the possibility of unidentified antibodies. Future studies should explore why differences in treatment between the two groups exist, and if slight differences in presentation influence clinical decision-making.